PENGARUH UPAH MINIMUM REGIONAL (UMR) DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP TINGKAT KEMISKINAN DI INDONESIA TAHUN 2006-2012 - B01107076, Tri Susilo (Jurnal Pembangunan dan Pemerataan, 2014)
The research entitled The Influence of Regional Minimum Wage and Human Development Index of the Level of Poverty In Indonesia Year 2006-2012. This purpose of this research is to determine whether there is influence of Inflation and Economic Growth to Unemployment Rate In Indonesia Year 2006-2012. To prove the hypothesis of the research with multiple linier regression analyzes used SPSS. Simultaneous regression calculation results showed that there is a significant relationship between the independent variable (Inflation and Economic Growth), to dependent variable (Unemployment Rate), while the partial regression calculation results showed that the only variable human development index significant negative effect on the level of poverty, which means any increase in human development index will be followed by a decrease in level of poverty. Value of coefficient of determination ( R2 ) of 0.336 or 33.6 % which indicates that the percentage of donations influence the ability of the independent variables (Regional Minimum Wage and Human Development Index ) on the dependent variable (level of poverty) , while the rest is influenced by the other independent variables were not examined . Keywords : Regional Minimum Wage, Human Development Index and Level of Poverty Â